If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(9/4)*x = 6/2 // - 6/2
(9/4)*x-(6/2) = 0
(9/4)*x-3 = 0
9/4*x-3 = 0 // + 3
9/4*x = 3 // : 9/4
x = 3/9/4
x = 4/3
x = 4/3
| 2x+15=5x+14 | | 0.7n=-77 | | 6-2b+3=1 | | 8y-13=-5(y-5) | | N/8=16 | | -5s-48=-a | | 3(4x-17)=3(x+7) | | 36x-45= | | -2(-7n+1)=5n-10 | | 46+21=11g | | 10-5m=45 | | 3(5y-5)-4= | | 17-11=2(x-7) | | 0.7t-3.2=1.7 | | h=-16t^2+60t+1 | | 7x+19-4x+4= | | -(3x+2)= | | -2-y=9 | | -105=8x | | 15x^2-x-54=0 | | 9j+2-j=8 | | ln(5)=ln(x+2)-ln(2) | | -6/-6 | | 0.5+6.4=4.9-18 | | 5v=9 | | 5x-16=x+6 | | -9x+5=-103 | | 3.2x+2.6=23 | | AX^2=2AX | | 7(x-3)=3x+15 | | 4(2x-3/4)=53 | | 455=O |